2014
DOI: 10.1017/thg.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Regular Exercise and Sedentary Behaviors

Abstract: Studies on the determinants of physical activity have traditionally focused on social factors and environmental barriers, but recent research has shown the additional importance of biological factors, including genetic variation. Here we review the major tenets of this research to arrive at three major conclusions: First, individual differences in physical activity traits are significantly influenced by genetic factors, but genetic contribution varies strongly over age, with heritability of leisure time exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 63 publications
6
70
0
Order By: Relevance
“…Taken together, our results are consistent with previous data on rodents 15,25,26 and humans 27,28 , which indicated that genetic predisposition plays a significant role in exercise participation. These results are also consistent with our previous suggestion 14 that genetic pleiotropy may partly explain the associations observed between high physical activity and mortality in our past epidemiological studies, which called for high quality intervention studies to analyse the true effects of physical activity on morbidity and mortality among initially healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Taken together, our results are consistent with previous data on rodents 15,25,26 and humans 27,28 , which indicated that genetic predisposition plays a significant role in exercise participation. These results are also consistent with our previous suggestion 14 that genetic pleiotropy may partly explain the associations observed between high physical activity and mortality in our past epidemiological studies, which called for high quality intervention studies to analyse the true effects of physical activity on morbidity and mortality among initially healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that genetic predisposition plays a significant role in exercise participation, which is consistent with previous data in rodents Kelly et al 2010;) and humans de Geus et al 2014). These results are also consistent with previous suggestion that genetic pleiotropy may partly explain the associations observed between high physical activity and mortality .…”
Section: Lifespansupporting
confidence: 93%
See 2 more Smart Citations
“…Because regular exercise behavior has been shown to be a heritable trait (de Geus et al 2014) it could be an important mediator of genetic effects on HRR and vagal rebound. Such hypotheses can be tested in twin models using a multivariate extension of the MZ and DZ twin (co)variance analysis.…”
Section: Introductionmentioning
confidence: 99%